II LATIN AMERICAN CONGRESS OF LIFE STYLE MEDICINE: II CONGRESO LATINOAMERICANO DE MEDICINA DE ESTILO DE VIDA - Medicine Association, Latin American Life Style (2018)
II LATIN AMERICAN CONGRESS OF LIFE STYLE MEDICINE 2018  We are pleased to direct you to invite you to the region's premium Lifestyle Medicine event, the “Second Latin American Congress of Lifestyle Medicine”, which will take place in Lima, Peru on 06 and 07 November 2018, at the Sheraton Hotel & amp; Convention Center. This international event is organized byLatin American Lifestyle Medicine Association: LALMA and has the strategic participation of universities and national and international companies.La Asociación Latinoamericana de Medicina de Estilo de Vida: LALMA (https://www.lalma.co) is the scientific medical professional organization that represents doctors and health professionals in the countries of Latin America and the Caribbean dedicated to the advancement and practice of Lifestyle Medicine; focused on the prevention, treatment and even the reversion of most chronic diseases, specifically addressing the true underlying causes.La Asociación Latinoamericana de Medicina de Estilo de Vida, it is a similar organization of American College of Lifestyle Medicine ACLM: (https://www.lifestylemedicine.org), de la Organización Europea de Medicina del Estilo de Vida EULM: (https://eulm.org) y forma parte de la Alianza Global de Instituciones de Medicina de Estilo de Vida LMGA:(https://lifestylemedicineglobal.org), counting in this way with all the scientific support of these structures. POST CONGRESS IMAGES